Treatment of acid rock drainage using a sulphate-reducing bioreactor with a limestone precolumn - Méndez, Gabriela (Environmental technology, 2023)
Sulphate reducing bacteria (SRB) offer promise for the treatment of mine waste due to their effectiveness removing toxic heavy metals as highly insoluble metal sulphides and their ability to generate alkalinity. The main objective of this study was to develop a treatment composed of a sulphate-reducing bioreactor with a limestone precolumn for the removal of Cu(II) from a synthetic ARD. The purpose of the limestone column was to increase the pH values and decrease the level of Cu in the effluent to prevent SRB inhibition. The system was fed with a pH-2.7 synthetic ARD containing Cu(II) (10-40 mg/L), sulphate (2000 mg/L) and acetate (2.5 g COD/L) for 150 days. Copper removal efficiencies in the two-stage system were very high (95-99%), with a final concentration of 0.53 mg/L Cu, and almost complete removal occurred in the limestone precolumn. In the same manner, the acidity of the synthetic ARD was effectively reduced in the limestone precolumn to 7.3 and the pH was raised in the bioreactor (7.3-8.0). COD consumption by methanogens was predominant from day 0-118, but SRB dominated at the end of the experiment (day 150) when the average COD removal and sulphide production were 74.8% and 61.7%, respectively. Study of the microbial taxonomic composition in the bioreactor revealed that Methanosarcina and Methanosaeta were the most prevalent methanogens while the genera Desulfotomaculum and Syntrophobacter were the dominant SRB. Among the SRB identified Desulfotomaculum intricatum (99% identity) and Desulfotomaculum acetoxidans (96%) were the most abundant sequences of bacteria capable of using acetate